Hubungan Kecemasan dengan Prokrastinasi Akademik Mahasiswa Prodi Pendidikan Masyarakat dalam Melaksanakan PLP FKIP UNRI - Siti Roidah; Wilson Wilson; Said Suhil Achmad (Ideas Publishing, 2022)
PLP atau Pengenalan Lapangan Persekolahan merupakan mata kuliah wajib dengan beban tugas dan SKS yang banyak, sehingga dalam pelaksanaannya, mahasiswa seringkali kebingunan untuk menentukan mana yang harus diselesaikan terlebih dahulu. Mahasiswa juga sering kesulitan dalam menyelesaikan semua tugas dari dosen pembimbing atau lembaga tempat mahasiswa melaksanakan PLP tepat waktu. Studi ini bertujuan menyelidiki hubungan antara kecemasan dan prokrastinasi akademik. Untuk mencapai tujuan tersebut, peneliti menggunakan metode penelitian kuantitatif dan strategi deskriptif. Hipotesis diuji dengan memanfaatkan teknik analisa linear berganada. Hasil pengujian terhadap hipotesis menunjukkan bahwa kecemasan memiliki hubungan yang signifikan dengan munculnya prokrastinasi akademik pada mahasiswa. The PLP is a mandatory field recognition activity with a high degree of duty and SKS load for a student body so that in the process it is not uncommon for students to feel confused as to which tasks should be done first, or set time to be on time for chores, whether they are given by the PLP advisor or the institution where students carry out the PLP. The purpose of this study is to find out if the cause of confusion that leads to a delay in this student is caused by the relationship between anxiety and academic procrastination, to which researchers aim to find out how high the anxiety related to the academic program is, Researchers figured that out by using a research ordinance (method) called a quantitative that USES a descriptive strategy. The hypotheses offered have been tested using an alternating linear analysis technique. Based on the results of the testing of the mortgage, it is claimed that the result of anxiety has a significant relationship to the development of the student's academic prejudice.